On the Ethnography of Media Production. An Interview with Georgina Born - Szczepanik, Petr (Iluminace, 2013)
An interview with British anthropologist and media ethnographer Georgina Born about her ethnographic method.
Keywords: anthropology and film; ethnography and film; media